Detection of aflatoxin producing Aspergillus flavus on peanut from the North of Vietnam by multiplex PCR - Hoi, Pham Xuan; Hieu, Dam Quang (Academia Journal of Biology, 2012)
Aflatoxins are among the most potent mutagenic, teratogenic, and carcinogenic natural compounds occurring in grains, foods and feeds. A numbers of studies have been focused on detection of aflatoxin producing aspergillus flavus. In this study, PCR approach - mediated method of detecting the aflatoxin-synthesizing genes in Aspergilus to identify Aflatoxin contamination degree in peanut from the North of Vietnam has been developed. A total of thirty strains of the A. flavus strains isolation on peanut from difference regions in the North of Vietnam and three A. niger strains, were subjected to PCR testing in an attempt to detect four genes, encoding for norsolorinic acid redutase (nor-1), versicolorin A dehydrogenase (ver-1), sterigmatocystin O-methyltransferase (omt-1) and a regulatory protein (apa-2), involved in aflatoxin biosynthesis. As a result from PCR reactions, nineteen strains of Aspergiluss flavus were shown to possess the four target DNA fragments, eight strains bearing less than the four target DNA fragments and others together with three A. niger strains were not contained any target DNA fragment suggesting that only strains of Aspergiluss flavus having PCR product of four target DNA fragments are aflatoxin producers. The nine strains of Aspergiluss flavus including seven strains containing four target DNA fragments, two strains did not contain any DNA fragment and 2 A. niger strains were subjected to multiplex PCR using the four pairs of primers complementing the coding region of the above genes. Interestingly, the four target DNA fragments were observed in all seven Aflatoxin producers, while others are not indicating that multiplex PCR is a suitable method for detection of Aflatoxin producing Aspergiluss flavus.